Peningkatan Kesadaran Lingkungan dan Pemberdayaan Ekonomi Melalui Program Sedekah Rosok di Desa Puhrubuh dalam Mencapai Tujuan Pembangunan Berkelanjutan (SDGs) - Tiyas, Vionada Pratiwi Ning; Lailatul, Ana; Dita, Erina; Nikmatul, Dewi; Fauzan, Ahmad; Ainin, Arfina Faiyatul (Welfare : Jurnal Pengabdian Masyarakat, 2024)
The Sedekah Rosok Program in Puhrubuh Village aims to increase environmental awareness and empower the community's economy as an effort to support the achievement of the Sustainable Development Goals (SDGs). This activity is carried out by educating the community about the importance of household waste management through sedekah rosok, which is the donation of used goods that have economic value. The PAR service method includes socialization, recycling training, and the formation of community-based sedekah rosok management groups. The results of the activity show an increase in community understanding of environmentally friendly waste management, a decrease in the volume of household waste, and the creation of new economic opportunities through the management of rosok which is processed into products with sales value. This program has succeeded in integrating aspects of environmental sustainability and economic empowerment, while strengthening community collaboration in supporting the goals of the SDGs, especially in the aspects of sustainable consumption and production and poverty alleviation.